2021
DOI: 10.1186/s12891-021-03962-x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical sagittal alignment after Prestige LP cervical disc replacement: radiological results and clinical impacts from a single-center experience

Abstract: Background Cervical disc replacement (CDR) has been widely used to treat one- and two-level cervical degenerative disc disease. Studies have shown the effectiveness of CDR in preserving range of motion (ROM) and delaying adjacent segment degeneration (ASD). Cervical sagittal alignment is an important factor affecting favorable clinical outcomes in cervical spine surgery. This study aimed to explore whether cervical sagittal alignment can be maintained after CDR and to identify the impact of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Static and dynamic lateral X-ray images were used to measure the cervical sagittal alignment and the parameters included C2-C7 Cobb angle, functional spinal unit (FSU) angle, range of motion (ROM) of C2-C7, the sagittal vertical axis (SVA) and T1 slope(T1S) [ 24 ]. The C2-C7 Cobb angle was formed between the lower endplate of the C2 vertebral body and the lower endplate of the C7 vertebral body.…”
Section: Methodsmentioning
confidence: 99%
“…Static and dynamic lateral X-ray images were used to measure the cervical sagittal alignment and the parameters included C2-C7 Cobb angle, functional spinal unit (FSU) angle, range of motion (ROM) of C2-C7, the sagittal vertical axis (SVA) and T1 slope(T1S) [ 24 ]. The C2-C7 Cobb angle was formed between the lower endplate of the C2 vertebral body and the lower endplate of the C7 vertebral body.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, CL loss and the FSU angle tend to shift the axial load from the posterior column to the anterior column. The change in cervical alignment potentially increases the mechanical stress in the anterior column and adjacent levels, which will also interfere with the biomechanical environment [ 36 ]. Moreover, the BMD and HU values were both inferior in the late postmenopausal group, which may partly lead to changes in cervical alignment and graft subsidence after ACDF [ 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these observations are limited by the absence of evaluation of the evolution of pain for the patients, as well as by the very short postoperative follow-up. Studies with much longer postoperative followups have demonstrated changes in cervical alignment in both arthrodesis (Hyun et al, 2017;Lan et al, 2019) and arthroplasty (Guérin et al, 2012;Kim et al, 2008;Wang et al, 2021). Some of these changes have been identified as risk factors for complications such as ASD (Katsuura et al, 2001;Xiong et al, 2020) and pseudarthrosis (Choi et al, 2017).…”
Section: Control and Clinical Subjectsmentioning
confidence: 99%